2002
DOI: 10.1109/68.986823
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and optimization of intensity noise reduction in spectrum-sliced WDM systems using a saturated semiconductor optical amplifier

Abstract: Abstract-Theoretical and experimental results on the reduction of the intensity noise in spectrum-sliced wavelength-divisionmultiplexing systems using a saturated semiconductor optical amplifier (SOA) are presented. The influence of the injected current and the input power to the saturated SOA on the noise reduction and its bandwidth are studied. The optimum condition for a high noise suppression ratio and a large bandwidth is derived. For the optimum operation of the SOA, an increase of 13.5 dB in the intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 5 publications
0
27
0
1
Order By: Relevance
“…The noise suppression offered by the saturated SOA is the result of small signal gain compression and intrachannel four-wave mixing (IC-FWM) [5], [8]. The spectral broadening due to the IC-FWM has been observed previously and can be significant depending on the input bandwidth and spectral shape [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The noise suppression offered by the saturated SOA is the result of small signal gain compression and intrachannel four-wave mixing (IC-FWM) [5], [8]. The spectral broadening due to the IC-FWM has been observed previously and can be significant depending on the input bandwidth and spectral shape [7].…”
Section: Resultsmentioning
confidence: 99%
“…One such approach uses the nonlinear gain compression of a saturated semiconductor optical amplifier (SOA) to suppress the intensity noise of the input thermal light [5]. This technique has the added benefit in that, ideally the SOA can also be used for signal modulation and amplification [6].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in [15], the extent of the achievable noise suppression is influenced by the operating point of the amplifier. To ensure optimum performance for our experiments, this dependence is measured as a function of amplifier drive current and input power.…”
Section: Characteristics Of the Noise-suppression Processmentioning
confidence: 99%
“…The noise also depends on the shape and width of the input spectrum slice; it decreases with increasing spectral width [14]. Studies have shown that this intensity noise can be significantly reduced by introducing a saturated SOA at the transmitter before modulation [8], [15] (block diagram shown in Fig. 1).…”
Section: Characteristics Of the Noise-suppression Processmentioning
confidence: 99%
“…One such a approach uses the nonlinear gain compression of a saturated SOA to suppress the intensity noise of the input thermal light [10]. This technique has the added benefit, in which ideally the SOA can also be used for signal modulation and amplification [11].…”
Section: Introductionmentioning
confidence: 99%